THE REVERSIBILITY OF ECONOMIC, SOCIAL AND CULTURAL RIGHTS IN CRISIS CONTEXT - Gómez Isa, Dr. Felipe (Teisė, 2015)
The current finacial crisis is having a significant impact on the enjoyment of socioeconomic rights in Europe but, in particular, in Southern countries such as Spain, Portugal, Italy or Greece. Even though International Human Rights Law imposes some limitations to the measures to be adopted in the face of the economic crisis, States do not generally approach the social cuts from a human rights angle. My paper will try to outline, firstly, the obligations assumed by States in the field of economic, social and cultural rights (ESCR) and, secondly, the limited opportunities to challenge retrogressive measures from an International Human Rights Law paradigm.